PERAMALAN CABAI BESAR DI KOTA MAKASSAR DENGAN METODE ARIMA - Andi Amran Asriadi; Firmansyah Firmansyah; Nailah Husain (Universitas Galuh, 2023)
Red chili is one of the commodities included in the volatile food group. This group is one of the components that make up inflation, which often contributes greatly in value compared to the price component regulated by the government. Forecasting is an activity to predict future events or conditions. This study aims to determine the performance of large red chili fluctuations in Makassar City and analyze the price forecasting for red chili using the Arima method for selecting the best selection in Makassar City. Analysis of the data used is ARIMA analysis using EViews12. The results showed that the diversity of onion price forecasts tended to show an increasing and slightly decreasing trend in each period, the actual price of large chilies for the period January 2021 to December 2025 in Makassar City when compared to the price of large chilies from the forecasting period January to December 2025, the fluctuations experienced an increase not too big. Seeing the difference in the highest price occurred in August of Rp. 43,391, and the lowest difference in December was Rp. 18,140. While forecasting the price of red chili with the ARIMA method, the best selection in Makassar City is the Model (1.1.1) which has the largest MSE of 15510.83, Model (4.0.0) which is the most moderate has MSE of 13867.02, and Model (4.1.1) the most small has an MSE of 13839.57.